Creating a family business : the genesis of Rogers Family Enterprises - Ward, John L., 1945- (SAGE knowledge. Cases., 2016)
Steven Rogers had always thought that someday he would like to own a business with one or both of his daughters. As his eldest daughter, Akilah, finished her final semester at Harvard Business School, she told Rogers that she would like to create with him a Chicago-based real estate venture that included buying, rehabbing and renting homes in the Englewood and South Shore neighborhoods of Chicago. Rogers quickly realized that his biggest challenge was how to equitably structure the ownership of the business. This case examines how Steven and Akilah set about planning their new project.